Proxy Index Derived From All Sky Imagers for Space Weather Impact on GPS. Issue 7 (21st July 2018) - Mushini, Sajan C.; Skone, Susan; Spanswick, Emma; Donovan, Eric; Najmafshar, Maryam
Abstract: Global Positioning System (GPS) signals passing through the auroral ionosphere, which exhibits multiscreen electron density structuring, maybe scintillated causing observation and possibly positioning errors. It is advantageous to determine the magnitude of GPS signal scintillation associated with a given level of auroral brightness observed around the signal's ionospheric pierce point (IPP). Such information would enable the exploitation of auroral image observations in space weather monitoring and help in assessment of impact on infrastructure/services reliant on GNSS. Studies have observed a general positive correlation between auroral brightness and GPS phase scintillation but not a definite one‐to‐one relationship. In this study a correlation coefficient of 0.38 is observed between the phase scintillation and the level of auroral arc brightness around the GPS signal's raypath for a data set of 292 events in the Canadian sector. Alternatively, a new pseudo‐scintillation index, Rate of change of Brightness index, is introduced in this study which is derived from the changing auroral brightness around the satellite's IPP. This Rate of change of Brightness index is highly positively correlated (correlation coefficient: 0.75) with GPS phase scintillation. Spatial and spectral relationships between auroral brightness around the satellite's IPP and phase scintillation were also analyzed. It is observed that probability of GPS signals experiencing phase scintillation is high when the auroral brightness around the satellite's IPP has dominant fluctuations in the frequency band ~0.06 to 0.16 Hz. These results indicate that GPS signal scintillation is related to the dynamics of the brightness around the satellite's IPP as the satellite signal propagates through the aurora. Key Points: Dynamics of auroral brightness are highly correlated with GPS phase scintillation New proxy GPS phase scintillation index derived from All Sky Imager